Capturing Tuberculinum Personalities Clinically- Study (Homoeopathy for All, 2023)
One of the most stubborn remedy  in our Materia medica which  is constitutionally deep acting,  pathogenetic product of disease. It  has been used to immunize people  who are affected from inherited  effect of tuberculosis. It is effective  to restore our vital reaction, along  with the pathological changes.  Intellectual curious individual  who tends to grasp the things  innovatively and works in effortless  manner, to achieve their goal. An  independent individual who doesn’t  expect anyone to work with them  neither get attached to anyone.  They are frivolous ones. People  of Tuberculinum personality are  unpredictable in their mood and  fun loving personality with relaxed  attitude, seems very attractive.  Childhood abuse in the past history  of the individual which may reflect  in the present scenario in the form  of various events. Weight of his past  events made him repulsive sometime.  Otherwise, he is predominantly an  attractive person with desired aim.  They are goal- oriented, intelligent,  also posses’ adaptability.
Keywords: stubborn; pathological; adaptability